Ternary WD40 Repeat-Containing Protein Complexes: Evolution, Composition and Roles in Plant Immunity - Miller, Jimi C.; Chezem, William R.; Clay, Nicole K. (Frontiers in Plant Science, 2016)
Plants, like mammals, rely on their innate immune system to perceive and discriminate among the majority of their microbial pathogens. Unlike mammals, plants respond to this molecular dialog by unleashing a complex chemical arsenal of defense metabolites to resist or evade pathogen infection. In basal or non-host resistance, plants utilize signal transduction pathways to detect “non-self,” “damaged-self,” and “altered-self”- associated molecular patterns and translate these “danger” signals into largely inducible chemical defenses. The WD40 repeat (WDR)-containing proteins Gβ and TTG1 are constituents of two independent ternary protein complexes functioning at opposite ends of a plant immune signaling pathway. They are also encoded by single-copy genes that are ubiquitous in higher plants, implying the limited diversity and functional conservation of their respective complexes. In this review, we summarize what is currently known about the evolutionary history of these WDR-containing ternary complexes, their repertoire and combinatorial interactions, and their downstream effectors and pathways in plant defense.